Estetika Kota dan Keberlanjutan Ekonomi: Evaluasi Kebijakan Relokasi Pedagang Kaki Lima (PKL) Ke Food Colony Kabupaten Pamekasan - arisa nadika nadika; Oktarizka Reviandani (Institut Pemerintahan Dalam Negeri, 2026)
The relocation policy of Street Vendors (PKL) to the Food Colony area in Pamekasan Regency is a local government effort to create more organized urban areas while simultaneously providing business locations for vendors. However, the implementation of this policy still faces various obstacles, particularly regarding the quiet condition of the area which lacks visitors. This research aims to evaluate the PKL relocation policy to the Food Colony area in Pamekasan Regency using William N. Dunn’s policy evaluation theory, which includes effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. This study employs a qualitative research method with a descriptive approach. Data collection techniques were conducted through observation, interviews, and documentation. Research informants consisted of the Pamekasan Regency Office of Cooperatives, SMEs, and Labor, the Civil Service Police Unit (Satpol PP), street vendors, and Food Colony visitors The results of the study indicate that the policy is aesthetically effective but economically ineffective due to a decrease in vendor revenue. There is an inefficiency between the large amount of infrastructure investment and the low daily economic activity. The indicators of adequacy and equity have not been met due to low consumer access and income inequality between kiosk positions. The government's responsiveness through bazaars is still temporary, and sociologically the policy is considered inappropriate for the characteristics of street vendors who depend on spontaneous buyers.